Unveiling FERONIA receptor kinase–mediated cellular mechanisms with a small-molecule inhibitor - Mengze Sun; Baiyan Lu; Ying Yang; Junping Fan; Weiwei Ren; Xiaonan Chu; Yihui Gao; Jun Wu; Jue Wang; Han Ke; Zhiwen Liu; Shaojun Dai; et al. (Proceedings of the National Academy of Sciences, 2025)
Since its initial identification as the receptor for Rapid Alkalinization Factor 1 (RALF1), FERONIA (FER) receptor kinase has emerged as a central signaling hub coordinating plant development, stress adaptation, and immune responses. Nevertheless, fundamental questions persist regarding the precise mechanisms of FER-mediated signal transduction and its context-dependent functional specialization in multicellular processes. Here, we develop Ferovicin (FRV), a small-molecule inhibitor that specifically disrupts FER kinase activity, thereby enabling mechanistic dissection of FER. Cocrystallization and mutational analysis show that FRV selectively binds to the ATP-binding pocket of the kinase domain of FER and inhibits its kinase activity. Assisted by the FRV tool and quantitative phosphoproteomics, we characterized a series of signaling pathways and networks regulated by RALF1 and FER. Notably, our analysis reveals that RALF1 activates FER through phosphorylation at Ser695, which subsequently inhibits H + -ATPase1/2 via phosphorylation at Ser899. This mechanism leads to apoplastic alkalinization and regulates cell expansion in the root meristem. Given the conservation of FRV binding sites in FER proteins across land plant species, FRV will serve as a valuable tool for dissecting FER signaling mechanisms as well as facilitating agricultural applications.